Unsteady MHD chemically reacting fluid through a porous medium bounded by a non-isothermal impulsively-started vertical plate: a numerical technique - Ahmed, Sahin; Kalita, Karabi (Journal of Naval Architecture and Marine Engineering, 2014)
A numerical modeling on MHD transient mass transfer by free convection flow of a viscous, incompressible, electrically-conducting, and Newtonian fluid through a porous medium bounded by an impulsively-started semi-infinite vertical plate in the presence of thermal radiation and chemical reaction of first order has been analyzed. The fluid is assumed optically thin gray gas, absorbing-emitting radiation, but a non-scattering medium. The dimensionless governing coupled, non-linear boundary layer partial differential equations are solved by an efficient, accurate, extensively validated and unconditionally stable finite difference scheme of the Crank-Nicolson type. The effects of the conduction-radiation parameter , chemical reaction and the porosity (K) on the velocity, temperature and concentration fields have been studied. The local skin friction, Nusselt number and the Sherwood number are also presented graphically and analyzed. Increasing magnetic parameter serves to decelerate the flow but increased temperatures and concentration values. It is found that the velocity is increased considerably with a rise in the porosity parameter (K) whereas the temperature and concentration are found to be reduced with increasing porosity (K). An increase in the porosity parameter (K) is found to escalate the local skin friction , Nusselt number and the Sherwood number . Possible applications of the present study include laminar aerodynamics, materials processing and thermo-fluid dynamics. DOI: http://dx.doi.org/10.3329/jname.v11i1.10269